Nerve growth factor in sympathetic ganglia and corresponding target organs of the rat: correlation with density of sympathetic innervation. - Korsching, S (1983)
A two-site enzyme immunoassay is described which does not suffer from artifacts inherent in previous assays and has the necessary high sensitivity to determine the endogenous levels of nerve growth factor (NGF) in the sympathetic nervous system and its target organs. Monoclonal and affinity-purified polyclonal antibodies against mouse NGF (mNGF) were covalently linked to glass beads as the first site and coupled to the enzyme beta-galactosidase as the second site. Detection of the fluorescent beta-galactosidase reaction product permitted the determination of 0.01-0.02 fmol of mNGF per assay. The recovery of mNGF added to homogenates varied between 50% and 100%, depending on the tissue. Rat superior cervical and stellate ganglia were found to contain (mean +/- SEM) 25 +/- 4 and 19 +/- 3 ng of NGF per g wet weight, respectively, and the densely innervated submandibular gland, heart atrium, and iris contained 0.5 +/- 0.1, 1.0 +/- 0.1, and 1.9 +/- 0.3 ng of NGF per g wet weight, respectively. Heart ventricle and skeletal muscle, which are poorly innervated by the sympathetic nervous system, did not contain detectable levels of NGF (less than 0.3 ng/g wet weight). Serum contained less than 0.05 ng of NGF per ml. The correlation between NGF levels and density of innervation is consistent with the concept that the production of NGF in target organs determines their density of innervation by the sympathetic nervous system.